Taking the transform of both sides gives
[tex]\mathcal L_s\{x''+8x'+15x\}=0[/tex]
[tex](s^2X(s)-sx(0)-x'(0))+8(sX(s)-x(0))+15X(s)=0[/tex]
where [tex]X(s)[/tex] denotes the Laplace transform of [tex]x(t)[/tex], [tex]\mathcal L_s\{x(t)\}[/tex]. Solve for [tex]X(s)[/tex] to get
[tex](s^2+8s+15)X(s)=2s+13[/tex]
[tex]X(s)=\dfrac{2s+13}{s^2+8s+15}=\dfrac{2s+13}{(s+3)(s+5)}[/tex]
Split the right side into partial fractions:
[tex]\dfrac{2s+13}{(s+3)(s+5)}=\dfrac a{s+3}+\dfrac b{s+5}[/tex]
[tex]2s+13=a(s+5)+b(s+3)[/tex]
If [tex]s=-3[/tex], then [tex]7=2a\implies a=\dfrac72[/tex]; if [tex]s=-5[/tex], then [tex]3=-2b\implies b=-\dfrac32[/tex]. So
[tex]X(s)=\dfrac72\dfrac1{s+3}-\dfrac32\dfrac1{s+5}[/tex]
Finally, take the inverse transform of both sides to solve for [tex]x(t)[/tex]:
[tex]x(t)=\dfrac72e^{-5t}-\dfrac32e^{-3t}[/tex]